Interaction Between Non-Coding RNAs and Interferons: With an Especial Focus on Type I Interferons - Ghafouri-Fard, Soudeh; Poornajaf, Yadollah; Dashti, Farzaneh; Hussen, Bashdar Mahmud; Taheri, Mohammad; Jamali, Elena (Frontiers in Immunology, 2022)
Interferons (IFNs) are a group of cellular proteins with critical roles in the regulation of immune responses in the course of microbial infections. Moreover, expressions of IFNs are dysregulated in autoimmune disorders. IFNs are also a part of immune responses in malignant conditions. The expression of these proteins and activities of related signaling can be influenced by a number of non-coding RNAs. IFN regulatory factors (IRFs) are the most investigated molecules in the field of effects of non-coding RNAs on IFN signaling. These interactions have been best assessed in the context of cancer, revealing the importance of immune function in the pathoetiology of cancer. In addition, IFN-related non-coding RNAs may contribute to the pathogenesis of neuropsychiatric conditions, systemic sclerosis, Newcastle disease, Sjögren’s syndrome, traumatic brain injury, lupus nephritis, systemic lupus erythematosus, diabetes mellitus, and myocardial ischemia/reperfusion injury. In the current review, we describe the role of microRNAs and long non-coding RNAs in the regulation of IFN signaling.